Impact of Bony Stress Injuries on Professional Basketball Performance. Issue 7 (21st July 2017) - Khan, Moin; Madden, Kim; Rogowski, Joseph P.; Stotts, Jeff; Burrus, Matthew Tyrrell; Samani, Marisa; Sikka, Robby Singh; Bedi, Asheesh
Objectives: Players in the National Basketball Association (NBA) subject their lower extremities to significant repetitive loading during the season as well as during off-season training. Little is known about the incidence and impact of lower extremity bony stress injuries in these athletes. Methods: Using the player injury database maintained by the NBA Players' Association, all bony stress injuries from 1992 to May 2016 were identified. Those not involving the lower extremity were excluded from the study. Stress fractures and stress reactions were grouped together. Number of games missed due to the injury as well as player statistics including points per game (ppg), assists per game (apg), steals per game (spg), and blocks per game (bpg) were collected from two years prior to the injury to two years after the injury. Results: 76 lower extremity bony stress injuries were identified involving 75 different NBA players with an average player age of 25.4 ± 4.1 years. 55.3% (42/76) involved the foot, 21.1% (16/76) involved the ankle or fibula, 17.1% (13/76) involved the tibia, and 6.6% (5/76) involved either the knee or patella. The majority of injuries occurred in season 82.9% (63/76) with half of the injuries occurring within the first 6 weeks of the season. 38.2% (29/76) of these injuries were managed surgically. An average of 25.1 ± 21.3 games were missed. 19.7% (15/76) of patients who sustained a stress fracture also had a subsequent injury. 29.2% (21/76) of players were not able to return to professional basketball after the season in which the injury was sustained; however, those who were able to return to the same level of play did not see a significant change in performance as measured by ppg, apg, spg, or bpg when comparing the season prior to the injury and either one or two years after the injury. Stress injuries to the foot carried the worst prognosis, 57.1% (12/21) of those unable to return to professional basketball sustained such an injury. Conclusion: While not extremely common in NBA players, lower extremity bony stress injuries may be career-ending. However, if they are able to return to the NBA following this injury, then their level of play should return to their pre-injury level.